The Comparative Efficacy of Emotionally Focused and Solution-Focused Couple Therapies in Remediating Marital Conflict: An Examination of Relational Dynamics and Forgiveness Trajectories - Pondeh Nezhadan, Fatemeh; Jahangiri, Mohammad Mehdi; Taghvaei, Davood (Advances in Nursing & Midwifery, 2024)
Abstract Introduction: Marital conflict often disrupts relational dynamics and hinders forgiveness, impacting the overall well-being of couples. This study aimed to comparatively evaluate the effectiveness of Emotionally Focused Couple Therapy (EFCT) and Solution-Focused Couple Therapy (SFCT) in improving relational dynamics and fostering forgiveness within couples experiencing marital conflict. Methods: This study adopted a quasi-experimental framework, implementing a pretest-posttest control group design, to investigate the efficacy of two therapeutic interventions. The study population comprised couples experiencing marital discord who sought assistance from family counseling centers in Ahvaz City during 2024. A total of 45 participants were selected via convenience sampling and subsequently assigned randomly to one of three groups: two experimental groups, receiving either EFCT or SFCT, and a control group. Both experimental interventions consisted of eight 90-minute sessions. Data were analyzed using analysis of covariance (ANCOVA) conducted within the SPSS version 26 statistical software. Results: The study’s results demonstrated that both EFCT and SFCT significantly improved relational dynamics and forgiveness in couples experiencing marital conflict, as shown by post-intervention assessments when compared to the control group (P<0.01). Notably, a direct comparison of the two therapies revealed a significant disparity in their impact on forgiveness, with EFCT exhibiting a substantially greater effect (P<0.05). Conversely, the two interventions did not differ significantly in their ability to enhance relational dynamics. Conclusions: This study confirms that both EFCT and SFCT are effective in improving marital relationships, but EFCT demonstrates a significantly stronger impact on fostering forgiveness. While both therapies enhance relational dynamics equally, EFCT appears to be particularly beneficial for addressing past relational wounds through facilitating forgiveness.